Exercise stress testing as a predictor of progression of early chronic Chagas heart disease - Viotti, Rodolfo Jorge (2005)
It is estimated that about four million people have chagasic heart disease in Latin America. The early detection of those patients who are likely to progress to more severe disease is necessary for appropriate treatment management to prevent further cardiac damage. The detection of ventricular arrhythmias is regarded as an expression of cardiac involvement in chagasic patients1 and it is a common finding during stress testing. The objective of this study was to ascertain whether stress testing has prognostic value for the progression of early chronic Chagas heart disease.